2009
DOI: 10.7150/ijbs.5.153
|View full text |Cite
|
Sign up to set email alerts
|

Activity of Chitosans in combination with antibiotics in Pseudomonas aeruginosa

Abstract: Chitosan and its derivative water soluble Chitosan oligosaccharide are used in a variety of applications in pharmaceutical preparations. In this study, 2 wild (ATCC 15729 and PAO1) and 2 mutant strains (PT121 and PT149) of P. aeruginosa are investigated for drug-drug interactions in vitro. 10 antimicrobial agents (antibiotics) are combined with different degree of deacetylated Chitosans and Chitosan oligosaccharide. All the chitosans show synergistic activity with sulfamethoxazole, a sulfonamide antimicrobial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
43
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(50 citation statements)
references
References 33 publications
5
43
0
Order By: Relevance
“…Many studies have demonstrated the efficacy of chitosan at different concentrations and exposure times for reducing the viability of different families of bacteria (Escherichia coli, Salmonella typhi, Salmonella paratyphi-A, Vibrio parahaemolyticus, Proteus vulgaris, Pseudomonas fluorescens, Pseudomonas aeruginosa, Listeria monocytogenes, Bacillus megaterium, Bacillus cereus, Staphylococcus aureus, Lactobacillus plantarum, Lactobacillus brevis, Lactobacillus bulgaricus, etc.) (No et al 2002;Tin et al 2009), fungi (A. niger, Alternaria alternata, Alternaria solani, Phomopsis asparagi, Rhizopus stolonifer, Rhizopus oryzae, Phytophthora capsici, Phytophthora parasítica, Verticillium dahlia, Colletotrichum orbiculare, Exserohilum turcicum, Pyricularia oryzae, Botrytis cinerea, Fusarium oxysporum, Fusarium graminearum, Fusarium sulphureum, Fusarium solani, Candida albicans, Neurospora crassa, Penicillium expansum, Penicillum digitatum, etc.) (Reddy et al 1998;Guerra-S 0 anchez et al 2009;Zhong et al 2007;Ziani et al 2009;Falcón et al 2008;Kong et al 2010;Yong-cai et al 2009;Lafontaine and Benhamou 1996;Lauzardo 2009;Rane and Hoover 1993;Ting et al 2007;Xu et al 2007;Palma-Guerrero et al 2009;Pacheco et al 2008) and parasites (Trichomonas gallinae, E. granulosus, Cryptosporidium parvum, Philasterides dicentrarchi, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have demonstrated the efficacy of chitosan at different concentrations and exposure times for reducing the viability of different families of bacteria (Escherichia coli, Salmonella typhi, Salmonella paratyphi-A, Vibrio parahaemolyticus, Proteus vulgaris, Pseudomonas fluorescens, Pseudomonas aeruginosa, Listeria monocytogenes, Bacillus megaterium, Bacillus cereus, Staphylococcus aureus, Lactobacillus plantarum, Lactobacillus brevis, Lactobacillus bulgaricus, etc.) (No et al 2002;Tin et al 2009), fungi (A. niger, Alternaria alternata, Alternaria solani, Phomopsis asparagi, Rhizopus stolonifer, Rhizopus oryzae, Phytophthora capsici, Phytophthora parasítica, Verticillium dahlia, Colletotrichum orbiculare, Exserohilum turcicum, Pyricularia oryzae, Botrytis cinerea, Fusarium oxysporum, Fusarium graminearum, Fusarium sulphureum, Fusarium solani, Candida albicans, Neurospora crassa, Penicillium expansum, Penicillum digitatum, etc.) (Reddy et al 1998;Guerra-S 0 anchez et al 2009;Zhong et al 2007;Ziani et al 2009;Falcón et al 2008;Kong et al 2010;Yong-cai et al 2009;Lafontaine and Benhamou 1996;Lauzardo 2009;Rane and Hoover 1993;Ting et al 2007;Xu et al 2007;Palma-Guerrero et al 2009;Pacheco et al 2008) and parasites (Trichomonas gallinae, E. granulosus, Cryptosporidium parvum, Philasterides dicentrarchi, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…mexT has been described as a mutational "hot spot," where mutations can contribute to global phenotypic changes in P. aeruginosa (6,(9)(10)(11). MexT is a transcriptional regulator of the MexEF-OprN efflux pump, which has been extensively characterized in the context of antimicrobial agents (12)(13)(14)(15). It has also been suggested that the MexEF-OprN pump is involved in the efflux of quorum-sensing (QS) signaling molecules, which could account for the attenuated virulence observed in strains with a functional MexT protein (5,16,17).…”
mentioning
confidence: 99%
“…In the past two decades, the interest in the biocidal properties of chitosan has greatly increased, which along with its nontoxic, biocompatible, hypoallergic, and biodegradable properties allow its use for biomed ical purposes as an alternative and/or auxiliary sub stance in antimicrobial therapy, especially against a number of bacterial strains resistant to classical antibi otics [2]. There are many publications in the literature con cerning the study of the biocidal properties of chitosan against gram positive bacteria, such as staphylococci [3][4][5][6][7] and bacilli [8,9] and gram negative bacteria, such as E. coli [3,[6][7][8][9][10][11], pseudomonades [2,10], and salmo nellae [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…There are many publications in the literature con cerning the study of the biocidal properties of chitosan against gram positive bacteria, such as staphylococci [3][4][5][6][7] and bacilli [8,9] and gram negative bacteria, such as E. coli [3,[6][7][8][9][10][11], pseudomonades [2,10], and salmo nellae [9,10]. Much more limited is the information on the antimicrobial activity of chitosan against Kleb siella pneumonia, among which we can mention the work on the cell ultrastructure under the action of the chitosan polymer [4].…”
Section: Introductionmentioning
confidence: 99%